(untitled) (Anuario Filosófico, 2018)
The work of Risieri Frondizi (1910-1983) is an important historical and philosophical connection between the Hispanic world and American philosophy. Frondizi shares with the classical American pragmatists, especially with John Dewey, (1) the same criticism of the starting point of modern philosophy, and (2) a defense of ‘experience’ as the proper basis for any philosophical inquiry. Moreover, (3) Frondizi can be read as making significant and original contributions to the history of doctrines such as pragmatism, which take ‘experience’ as their starting point.